Electrocatalytic Properties of Calcium Titanate, Strontium Titanate, and Strontium Calcium Titanate Powders Synthesized by Solution Combustion Technique - Oratai Jongprateep; Nicha Sato; Ratchatee Techapiesancharoenkij; Krissada Surawathanawises (Advances in Materials Science and Engineering)
Calcium titanate (CaTiO3), strontium titanate (SrTiO3), and strontium calcium titanate (SrxCa1−xTiO3) are widely recognized and utilized as dielectric materials. Their electrocatalytic properties, however, have not been extensively examined. The aim of this research is to explore the electrocatalytic performance of calcium titanate, strontium titanate, and strontium calcium titanate, as potential sensing materials. Experimental results revealed that CaTiO3, SrTiO3, and Sr0.5Ca0.5TiO3 powders synthesized by the solution combustion technique consisted of submicrometer-sized particles with specific surface areas ranging from 4.19 to 5.98 m2/g. Optical bandgap results indicated that while CaTiO3 and SrTiO3 had bandgap energies close to 3 eV, Sr0.5Ca0.5TiO3 yielded a lower bandgap energy of 2.6 eV. Cyclic voltammetry tests, measured in 0.1 M sodium nitrite, showed oxidation peaks occurring at 0.58 V applied voltage. The highest peak current was observed in Sr0.5Ca0.5TiO3 powder. The superior electrocatalytic performance of Sr0.5Ca0.5TiO3 might be attributed to lower bandgap energy, which consequently facilitates higher electron transfer. Electrocatalytic performance of Sr0.5Ca0.5TiO3 was subsequently reexamined in a wider concentration range of sodium nitrite. The results revealed that the material responded linearly to nitrite solution in the range of 0.1 mM to 0.1 M and exhibited sensitivity ranging from 3.117 to 0.040 μA/mM, in the entire tested nitrite concentrations. The results suggest that Sr0.5Ca0.5TiO3 could also be used for nitrite detection.